1999
DOI: 10.1016/s0006-3495(99)76905-5
|View full text |Cite
|
Sign up to set email alerts
|

The Quantum Mixed-Spin Heme State of Barley Peroxidase:A Paradigm for Class III Peroxidases

Abstract: Electronic absorption and resonance Raman (RR) spectra of the ferric form of barley grain peroxidase (BP 1) at various pH values, at both room temperature and 20 K, are reported, together with electron paramagnetic resonance spectra at 10 K. The ferrous forms and the ferric complex with fluoride have also been studied. A quantum mechanically mixed-spin (QS) state has been identified. The QS heme species coexists with 6- and 5-cHS hemes; the relative populations of these three spin states are found to be depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
120
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(139 citation statements)
references
References 57 publications
14
120
0
1
Order By: Relevance
“…The most striking difference between the spectra of native and Ca 2ϩ -depleted HRPC is the higher frequencies of the core size marker bands of the Ca 2ϩ -depleted form. This immediately indicates the presence of a QS heme state, which is more fully expressed compared with that of the native protein having a greater proportion of IS in the quantum mechanical admixture, since no bands due to an LS heme were detected in the corresponding absorption spectrum (22)(23)(24). All subsequent reference to the QS state of the Ca 2ϩ -depleted enzyme will be in regard to this fully expressed QS state and not that of the native protein in which only a low level of IS is apparently present.…”
Section: Electronic Absorption and Resonance Raman Of Ferric Enzymes-mentioning
confidence: 94%
“…The most striking difference between the spectra of native and Ca 2ϩ -depleted HRPC is the higher frequencies of the core size marker bands of the Ca 2ϩ -depleted form. This immediately indicates the presence of a QS heme state, which is more fully expressed compared with that of the native protein having a greater proportion of IS in the quantum mechanical admixture, since no bands due to an LS heme were detected in the corresponding absorption spectrum (22)(23)(24). All subsequent reference to the QS state of the Ca 2ϩ -depleted enzyme will be in regard to this fully expressed QS state and not that of the native protein in which only a low level of IS is apparently present.…”
Section: Electronic Absorption and Resonance Raman Of Ferric Enzymes-mentioning
confidence: 94%
“…11,[18][19][20] Namely, the origin of this unusual heme configuration, also observed in class III plant peroxidases, cytochromes c 0 and catalase peroxidases (e.g. KatG), is not well understood.…”
mentioning
confidence: 99%
“…KatG), is not well understood. 11,[18][19][20] We have previously demonstrated that it could be observed in B-, but not in A-type DyPs, and that its abundance sensitively depends on the pH, temperature, and physical state of the enzyme. 10 Here we provide direct experimental evidence that the QS species is capable of reacting with H 2 O 2 and that it is therefore, most likely catalytically competent in PpDyP.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on structural divergence, the plant peroxidase superfamily is subdivided into three classes. BP1 belongs to class III, typified by the classical horseradish peroxidase isoenzyme C (HRPC) 135 . In common with other heme-containing peroxidases, BP1 catalyzes the following multistep reaction 271 The rate of the BP1 reaction with hydrogen peroxide is very slow at a pH above 5 and increases as the pH is lowered to 3.…”
Section: Peroxidases (Pr-9)mentioning
confidence: 99%